“Suddenly we were all online": perceptions and practices experienced by faculty and students during emergency teaching - Paiva, Ana Maria Videira (2021)
This paper is integrated in Research Project Digital Transformation in Higher Education in a time of Pandemic, nº PTIN/UID4372-LE@D/032020, Laboratory of Distance Education and eLearning, UID 4372/FCT.